European Narratives on Remote Working and Coworking During the COVID-19 Pandemic (Springer Nature, 2023)
This open access book offers a multidisciplinary and comprehensive perspective regarding the immediate and long-term effects of the Covid-19 pandemic on coworking spaces in the European Region. The current pandemic has imposed several effects on work and spaces for work. Some are immediate effects and will last for a short time (such as the closing down of the space), some will last longer (namely, the reorganisation of the space to meet the physical distancing), and some will stay for a long time (remote working and hybrid working). Although the literature on coworking spaces and the effects of the pandemic is growing fast, empirical studies are yet limited. Within this context, this book seeks a twofold aim: (i) to contribute to the fast-growing literature on coworking space and their effects at different scales; (ii) to present a multidisciplinary perspective about the effects of the yet-lasting Corona-pandemic effects on the patterns of remote working and consequently on coworking spaces, as the most diffused form of new working spaces.